ANALYSIS OF TAXI SERVICE ORGANIZING AND REGULATION FOR BAKU CITY - Vilayat VAILIYEV; Fuad DASHDAMIROV; Azer GURBANOV; Aynura ISMAYILOVA (Scientific Journal of Silesian University of Technology. Series Transport)
With the expansion of the use of digital technologies, the nature of almost all service industries has changed. Taxi services are no exception. The use of mobile applications, and the creation of call centres, have simplified the access of passengers to taxis and created a new situation. Despite this, with the emergence of a new situation, new problems appeared. This article aims to study taxi services organization and regulation. Thus, surveys were conducted to study attitudes towards offered services for passengers and drivers, the main participants in the taxi market. The questionnaires are aimed at studying the satisfaction of passengers and the attitude of drivers to working conditions. The total weight of using a taxi in comparison with other types of urban transport is determined. The frequency and main reasons for requests for taxi services were identified. This paper also studied the degree of use of mobile applications for calling a taxi and the distribution of orders between taxi companies. Surveys among drivers were mainly aimed at studying the mode of their work and their attitude to the conditions offered by taxi companies. To solve the identified problems, an appropriate regulation method through a single digital platform was proposed.